Ginsenoside Rg2 Ameliorates Myocardial Ischemia/Reperfusion Injury by Regulating TAK1 to Inhibit Necroptosis - Li, Yao; Hao, Hao; Yu, Haozhen; Yu, Lu; Ma, Heng; Zhang, Haitao (Frontiers in Cardiovascular Medicine, 2022)
Necroptosis contribute to the pathogenesis of myocardial ischemia/reperfusion (MI/R) injury. Ginsenoside Rg2 has been reported to have cardioprotective effects against MI/R injury, however, the underlying mechanism remains unclear. This work aimed to investigate the effect of ginsenoside Rg2 on necroptosis induced by MI/R and to explore the mechanism. In this study, Hypoxia/Reoxygenation (H/R) injury model was established in H9c2 cells. In vivo, male C57/BL6 mice were subjected to myocardial ischemia 30min/reperfusion 4h. Rg2 (50 mg/kg) or Vehicle were intravenously infused 5 min before reperfusion. Cardiac function and the signaling pathway involved in necroptosis was investigated. Compared with H/R group, Rg2 significantly inhibited H/R induced cardiomyocyte death. Rg2 treatment effectively inhibited the phosphorylation of RIP1, RIP3 and MLKL in H/R cardiomyocytes, and inhibited RIP1/RIP3 complex (necrosome) formation. In mice, Rg2 treatment manifested significantly lower I/R-induced myocardial necroptosis, as evidenced by decrease in phosphorylation of RIP1, RIP3 and MLKL, inhibited LDH release and Evans blue dye (EBD) penetration. Mechanically, an increased level of TNFα, IL-1β, IL-6 and MCP-1were found in MI/R hearts, and Rg2 treatment significantly inhibit the expression of these factors. We found that TNFα induced phosphorylation of RIP1, RIP3 and MLKL was negatively correlated with TAK1 phosphorylation, and inhibition of TAK1 phosphorylation led to necroptosis enhancement. More importantly, Rg2 treatment significantly increased TAK1 phosphorylation, enhanced TAK1 binding to RIP1 while inhibited RIP1/RIP3 complex, ultimately reducing MI/R induced necroptosis. These findings highlight new mechanism of Rg2 induced cardioprotection: reducing the formation of RIP1/RIP3 necrosome by regulating TAK1 phosphorylation to block necroptosis induced by MI/R.